“Sobre llovido, mojado”. Problems, strategies, and demands of the Argentine popular, social, and solidarity economy during the pandemic - Deux-Marzi, María Victoria (2023)
The emergency caused by the COVID-19 pandemic reactivated numerous debates on the social protections required for distinct labor groups and the need to guarantee work and income for the population. This article focuses on the experiences of people who work without ties to an employer and who self-identify as part of the popular, social, and solidarity economy (EPSS) in Argentina. It aims to contribute to the academic debate by identifying the conditions that favored the sustainability and organization of their work beyond the context of the emergency. In particular, we seek to examine whether the situation opened up by the pandemic led to new processes of recognition, institutionalization, and protection for these labor groups or not. A qualitative research process was developed based on interviews with representatives of 14 organizations of EPSS of Greater Rosario (primary sources) and the review of emergency measures and programs implemented by the three levels of government – national, provincial, and local – beginning with the declaration of the health emergency until December 2021 (secondary sources). In the final reflections, the main results are highlighted, positing that the state’s responses did not give rise to new institutions, rights, and protections, but rather “organized” and “administered” the institutionality that already existed.